Biomacromolecule‐Fueled Transient Volume Phase Transition of a Hydrogel. Issue 33 (3rd May 2022) - Nakamoto, Masahiko; Kitano, Shiro; Matsusaki, Michiya
Abstract: A metabolic cycle‐inspired hydrogel which exhibits the biomacromolecule‐fueled transient volume phase transition is reported. This hydrogel has the affinity and digestive capacity for a fuel α‐poly‐L‐lysine by incorporating acrylic acid and trypsin. The hydrogel captured fuel and transiently shrank owing to the construction of electrostatic cross‐linkages. This process was inherently connected with the digestion of these cross‐linkages and the release of oligo‐lysine as waste, which induced the reswelling of the hydrogel at equilibrium. The transient volume change of the hydrogel realized the fuel‐stimulated transient release of a payload. This study provides a strategy for engineering materials with biomacromolecule‐fueled dynamic functions under the out‐of‐equilibrium condition. Abstract : Artificial materials that perform work under out‐of‐equilibrium conditions have attracted significant attention. A metabolic cycle‐inspired hydrogel which exhibits the biomacromolecule‐fueled transient volume phase transition was developed. The hydrogel was prepared by introducing two inherently connected functions that are affinity and digestive capacity for fuel. The system could also be exploited to realize the fuel‐stimulated transient release of the payload.